Comparative evaluation of underlying causes of death processed by the Automated Classification of Medical Entities and the Underlying Cause of Death Selection Systems Avaliação comparativa das causas básicas de morte processadas pelos Sistemas "Automated Classification of Medical Entities" e de Seleção de Causa Básica - Augusto H. Santo; Celso E. Pinheiro; Eliana M. Rodrigues (Universidade de São Paulo, 1998)
INTRODUCTION: The correct identification of the underlying cause of death and its precise assignment to a code from the International Classification of Diseases are important issues to achieve accurate and universally comparable mortality statistics These factors, among other ones, led to the development of computer software programs in order to automatically identify the underlying cause of death. OBJECTIVE: This work was conceived to compare the underlying causes of death processed respectively by the Automated Classification of Medical Entities (ACME) and the "Sistema de Seleção de Causa Básica de Morte" (SCB) programs. MATERIAL AND METHOD: The comparative evaluation of the underlying causes of death processed respectively by ACME and SCB systems was performed using the input data file for the ACME system that included deaths which occurred in the State of S. Paulo from June to December 1993, totalling 129,104 records of the corresponding death certificates. The differences between underlying causes selected by ACME and SCB systems verified in the month of June, when considered as SCB errors, were used to correct and improve SCB processing logic and its decision tables. RESULTS: The processing of the underlying causes of death by the ACME and SCB systems resulted in 3,278 differences, that were analysed and ascribed to lack of answer to dialogue boxes during processing, to deaths due to human immunodeficiency virus [HIV] disease for which there was no specific provision in any of the systems, to coding and/or keying errors and to actual problems. The detailed analysis of these latter disclosed that the majority of the underlying causes of death processed by the SCB system were correct and that different interpretations were given to the mortality coding rules by each system, that some particular problems could not be explained with the available documentation and that a smaller proportion of problems were identified as SCB errors. CONCLUSION: These results, disclosing a very low and insignificant number of actual problems, guarantees the use of the version of the SCB system for the Ninth Revision of the International Classification of Diseases and assures the continuity of the work which is being undertaken for the Tenth Revision version. INTRODUÇÃO: A identificação correta da causa básica de morte e a atribuição de código preciso da Classificação Internacional de Doença à mesma são importantes para a obtenção de estatísticas de mortalidade confiáveis e passíveis de comparabilidade universal. Estes fatores, dentre outros, levaram ao desenvolvimento de programas de computador para identificar automaticamente a causa básica de morte. OBJETIVO: Este trabalho teve a finalidade de comparar a causa básica de morte identificada respectivamente pelos programas Automated Classification of Medical Entities (ACME) e pelo Sistema de Seleção de Causa Básica de Morte (SCB). MATERIAL E MÉTODO: O arquivo para a entrada de dados sobre causas de morte (input file) para o Sistema ACME contendo registros de 129.104 declarações de óbito de mortes ocorridas no estado de São Paulo de junho a dezembro de 1993 foi utilizado para o processamento da causa básica pelo SCB. Os problemas identificados pelo processamento dos registros do mês de junho foram considerados para o aprimoramento do sistema SCB. RESULTADOS: Foram encontras 3.278 causas básicas de morte identificadas de modo diferente pelos programs ACME e SCB. Essas diferenças foram atribuídas à falta de resposta adequada a janelas de diálogo durante o processamento pelo SCB, a óbitos por doenças devida a vírus da imunodeficiência adquirida para os quais não havia tabelas de decisão específicas, a erros de codificação e/ou digitação e a problemas propriamente ditos. A análise pormenorizada deste últimos mostrou que, em sua maioria, as causas básicas processadas pelo sistema SCB estavam corretas, que diferentes interpretações das regras de mortalidade foram dadas pelos sistemas comparados, que alguns problemas particulares não tiveram explicação adequada por falta de documentação sobre os mesmos e que uma menor proporção de problemas consistia de erros do SCB. CONCLUSÕES: O número pequeno e praticamente insignificante de problemas encontrados garante o uso da versão do SCB para a Nona Revisão da Classificação Internacional de Doenças e assegura a continuidade dos trabalhos relativos à sua versão para a Décima Revisão.